1957
DOI: 10.1084/jem.106.5.767
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dietary Magnesium on Cardiac and Renal Lesions of Young Rats Fed an Atherogenic Diet

Abstract: PLATES 93 TO 95(Received for publication, May 20, 1957) Evidence has been presented that the feeding of an atherogenic diet to weanling male rats increased the requirement for magnesium and that the atherosclerosis produced was made less severe or was delayed by the administration of large amounts of dietary magnesium (1).The present communication describes the morphology of the renal lesions found in rats fed the atherogenic diet (1). These lesions are consistent with magnesium deficiency despite the fact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

1961
1961
1992
1992

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(7 citation statements)
references
References 13 publications
1
5
0
1
Order By: Relevance
“…Rats feeding on the very iodine-rich AOAC mixture containing lower amounts of magnesium, zinc and fluorine developed a more pronounced nephrocalcinosis than those on the basal diet containing minerals according to Müller [9], Magnesium deprivation is known to promote the development of nephrocalcinosis in the rat [3] but it is doubtful if the level of magnesium obtained with the AOAC salt (29 mg%) is low enough to explain the higher frequency of calcification in this group. However, pronounced renal calcification has been observed in male rats fed an atherogenic diet containing 10% protein, 1% cholesterol, 0.3% cholic acid, 20% fat and 24 mg% magnesium [3], although only a slight reduction in the nephrocalcinosis was brought about by increasing the dietary magnesium content to 48 mg%, i.e. the same level of magnesium as in diets supplemented according to M uller [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rats feeding on the very iodine-rich AOAC mixture containing lower amounts of magnesium, zinc and fluorine developed a more pronounced nephrocalcinosis than those on the basal diet containing minerals according to Müller [9], Magnesium deprivation is known to promote the development of nephrocalcinosis in the rat [3] but it is doubtful if the level of magnesium obtained with the AOAC salt (29 mg%) is low enough to explain the higher frequency of calcification in this group. However, pronounced renal calcification has been observed in male rats fed an atherogenic diet containing 10% protein, 1% cholesterol, 0.3% cholic acid, 20% fat and 24 mg% magnesium [3], although only a slight reduction in the nephrocalcinosis was brought about by increasing the dietary magnesium content to 48 mg%, i.e. the same level of magnesium as in diets supplemented according to M uller [9].…”
Section: Discussionmentioning
confidence: 99%
“…Cousins and Geary [1] concluded that both estrogens and a dietary factor were implicated in the etiology of this condition. Several authors have demonstrated a lower incidence of renal calculi in rats fed diets containing additional casein [3][4][5]. Also, addition of gluten as well as supple mentation with methionine, cystine, glutamic acid and ammonium sulfate was effective in reducing the nephrocalcinosis [5], This was interpreted as an effect of acidification of the tubular fluid leading to an increased solubility of calcium phosphate [5].…”
Section: Introductionmentioning
confidence: 99%
“…After testing a number of minerals often present in hard water, Neal & Neal (1962) reported that the addition of 3 yo magnesium sulphate to the drinking water of the cholesterol-fed rabbit prevents the development of gross plasma turbidity and atheroma. Conversely, magnesium deficiency in the cholesterol-fed rat and monkey (Cebus futuellu) leads to increased serum cholesterol and accentuated lipid deposition in arteries (Gottlieb, Broitman, Vitale & Zamcheck, 1959;Hellerstein et al, 1957; Vitale, Velez, Guzman & Correa, 1963). Excess dietary magnesium lactate, however, has neither hypocholesterolaemic nor anti-atherogenic actions in the cholesterol-fed rabbit (Adams, Bayliss, Ibrahim & Roper, 1964).…”
Section: ( 5 ) Hormones Vitamins and Mineralsmentioning
confidence: 99%
“…6 (1966) erzeugender Diäten verstärkt (34,37). Umgekehrt wird durch Thyroxinapplikation normaler oder bereits erhöhter Blutdruck gesteigert (4), die experimentell erzeugte Aortalipoidose aber ver ringert (5,16).…”
unclassified